Quantifying Conceptual Novelty in the Biomedical Literature - Mishra, Shubhanshu; Torvik, Vetle I. (D-Lib magazine, 2016)
Introduces several measures of novelty for a scientific article in MEDLINE based on the temporal profiles of its assigned Medical Subject Headings (MeSH). Characterises temporal profiles for all MeSH terms (and pairs of MeSH terms) empirically and models as logistic growth curves. Captures a paper's novelty by its youngest MeSH (and pairs of MeSH) as measured in years and volume of prior work. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.